Structural and functional body components in athletic health and performance phenotypes - Silva, A. M. (European Journal of Clinical Nutrition, 2018)
Advances in body composition assessment enable a detailed body composition analyses and the respective organization at different levels. Sports-related professionals are interested in understanding how and which body components are relevant for improving performance, prevent injury risk, and monitor athletic health. The aim of this review is to propose an integrative model that links performance, injury risk, and athletic health with body components, and to report their crosssectional and longitudinal associations. Cross-sectional studies reveal that endurance athletes with higher fat mass (FM) show a longer race time, whereas a higher fat-free mass benefits power and strength-related tasks. Longitudinal studies indicated that increases in intracellular water, assessed through dilution techniques, were associated with power and strength improvements, independently of weight and lean-soft-tissue changes. There is evidence that athletes involved in weightsensitive sports restrict energy intake, thus reducing energy availability (EA) and compromising bone health (Female Athlete Triad). To counteract the low EA and related negative energy balance, metabolic adaption (MA) occurs to promote energy conservation. Currently, reference values for body composition assessment using anthropometry and DXA are available for a few sports, according to sex. More research is needed to develop a functional body composition profile according to sportsspecific requirements.